Kanban and just- in- time at Tokyo; managemenet begins at the workplace (Productivity Press, 1985)
Toyota's world-renowned success proves that with kanban, the Just-In-Time production system (JIT) makes most other manufacturing practices obsolete. This simple but powerful classic is based on seminars given by JIT creator Taiichi Ohno to introduce Toyota's own supplier companies to JIT. It shows how to implement the world's most efficient production system. A clear and complete introduction.